THE APPLICATION OF HERRING BONE METHOD IN TEACHING READING COMPREHENSION (A Research Conducted at first Grade of SMA Negeri 1 Telaga Biru) - Mestari, Sri Agriyanti; Luwiti, Sri Rumiyatiningsih; Tanaiyo, Yuliyanti (Pascasarjana, Universitas Negeri Gorontalo, 2022)
This research aims to find out whether the application of Herring Bone method can improve students’ reading comprehension on Recount text at SMA Negeri 1 Telaga Biru. It was conducted to first grade particularly class X IPA 1 as the sample of this research. The researcher conducted a one group pre-test post-test design in order to find out the significant difference of students’ reading comprehension before and after being taught through Herring Bone method. The quantitative method is applied for this research because this type of research is explaining a phenomenon by collecting numerical data that are analyzed statistically. As the result, the application of Herring Bone method can improve students’ reading comprehension on narrative text. It showed based the result of mean score in pre-test is 15,3 and in post-test increased to 17,9. In addition, the application of this method helps the students arrange the idea in comprehending the content of text, made the students became active and more interesting in reading activity.